2005
DOI: 10.1111/j.1469-8137.2005.01630.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drought on productivity and water use efficiency in 29 genotypes of Populus deltoides×Populus nigra

Abstract: Summary• We examined the relationships among productivity, water use efficiency ( WUE) and drought tolerance in 29 genotypes of Populus × euramericana ( Populus deltoides × Populus nigra ), and investigated whether some leaf traits could be used as predictors for productivity, WUE and drought tolerance.• At Orléans, France, drought was induced on one field plot by withholding water, while a second plot remained irrigated and was used as a control. Recorded variables included stem traits (e.g. biomass) and leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
319
4
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(365 citation statements)
references
References 44 publications
23
319
4
3
Order By: Relevance
“…Previous studies indicated that these differences among poplar genotypes are driven by variation in g s (Fichot et al., 2011; Monclus et al., 2006; Navarro et al., 2014). The differences in g s among genotypes were clearly manifested in the values of E leaf and E stem observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that these differences among poplar genotypes are driven by variation in g s (Fichot et al., 2011; Monclus et al., 2006; Navarro et al., 2014). The differences in g s among genotypes were clearly manifested in the values of E leaf and E stem observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence of a significant genotypic variability for productivity and for Δ 13 C (used as a proxy of WUE) in poplars and other tree species has been demonstrated, including a negative relationship between biomass and Δ 13 C (Cassasoli et al., 2004; Guehl, Nguyen‐Queyrens, Loustau, & Ferhi, 1994; Monclus et al., 2009; Zhang, Zang, & Li, 2004) or an opposite pattern (Marron et al., 2005; Rae, Robinson, Street, & Taylor, 2004). WUE in poplars is highly heritable (Monclus et al., 2005, 2006) and there is generally no trade‐off between WUE and productivity. Thus, the relationship between productivity and WUE seems to be a function of the genetic background and probably of the parentage, although further studies are needed to identify the genomic determinants of productivity and WUE via a QTL (Quantitative Trait Loci) approach.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, positive genetic association between a number of droughtinducible candidate genes and CID in needles was found. The CID, applied to different plant tissues (generally needles or leaves but also wood), is a timeintegrated estimator of photosynthetic WUE, that is, the ratio between net CO 2 assimilation and stomatal conductance, and has been extensively used to compare response to drought in plants, including forest trees (reviewed in Warren et al, 2001;Dawson et al, 2002;Adams and Kolb, 2004;Monclus et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Wageningen, The Netherlands), placed in pots at an angle of 45° and allowed to equilibrate for 4 hours under vacuum (Cattani et al, 2006 (Monclus et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%